2022
DOI: 10.1002/aet2.10756
|View full text |Cite
|
Sign up to set email alerts
|

Sex, gender, and the opioid epidemic: Crucial implications for acute care

Abstract: Introduction: The opioid epidemic continues to escalate in the United States, exacerbated significantly by the COVID-19 pandemic. Necessary steps in acute care medicine to expand efforts to combat this epidemic involve increased emergency department engagement of patients with opioid use disorder (OUD) and an incorporation of evolving sex-and gender-based factors that affect this disease presentation and management course. Methods & Aims: An ever-increasing amount of peer-reviewed, evidence-based literature ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…From 2019 to 2020 (during the COVID-19 pandemic), the Center for Disease Control (CDC) reported a 31% increase (up to 28.3 per 100,000) in the age-adjusted rate of overdose deaths, with 75% of those deaths involving an opioid (Death Rate Maps & Graphs | Drug Overdose | CDC Injury Center, 2022). In 2018, the opioid-involved death rate was two to three times higher for men than women (Wilson et al, 2020), which may reflect the higher prevalence of opioid use in men (Walter et al, 2022), however the incidence of opioidinvolved deaths has increased at twice the rate in women (Back et al, 2011). The primary cause of death from opioid overdose is respiratory depression and hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…From 2019 to 2020 (during the COVID-19 pandemic), the Center for Disease Control (CDC) reported a 31% increase (up to 28.3 per 100,000) in the age-adjusted rate of overdose deaths, with 75% of those deaths involving an opioid (Death Rate Maps & Graphs | Drug Overdose | CDC Injury Center, 2022). In 2018, the opioid-involved death rate was two to three times higher for men than women (Wilson et al, 2020), which may reflect the higher prevalence of opioid use in men (Walter et al, 2022), however the incidence of opioidinvolved deaths has increased at twice the rate in women (Back et al, 2011). The primary cause of death from opioid overdose is respiratory depression and hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…This relative burden, accompanied by financial strain, (female participants were less likely to be employed or have financial needs met) may result in a sense of depression or ‘no energy for life.’ While historically, men have accounted for the majority of illicit drug use and opioid overdoses, the past decade in particular has seen women increasingly impacted. Gender-specific differences in OUD, as well as OUD treatment outcomes, have been demonstrated previously and deserve continued focus and consideration ( Walter et al., 2022 ). Violence exposure was another subjectively-reported category with disproportionate representation of female participants.…”
Section: Discussionmentioning
confidence: 81%
“…Our results also demonstrated the presence of racial disparities as fewer Black people received naloxone prescriptions than whites. Despite being historically and stereotypically considered a disease impacting majority white, male patients in the United States, recent demographic data of people with OUD have shifted to include increasing percentages of women and racial minorities [ 12 , 30 ]. Another study also showed opioid-related deaths among Black people rose 38% from 2018 to 2019 while rates for other racial groups did not significantly change [ 31 ].…”
Section: Discussionmentioning
confidence: 99%